Invalidation of fMRI experiments secondary to neurovascular uncoupling in patients with cerebrovascular disease. Issue 5 (2nd February 2017) - Para, Andrea E.; Sam, Kevin; Poublanc, Julien; Fisher, Joseph A.; Crawley, Adrian P.; Mikulis, David J.
Abstract : Purpose: Blood oxygen level‐dependent (BOLD) functional magnetic resonance imaging (fMRI) is a technique used to infer neuronal activity from the observed changes in blood flow. Cerebrovascular reactivity (CVR) is the ability of arterioles to increase blood flow in response to vasodilatory stimulus. We hypothesize that in areas of disease where there is exhausted vascular reserve and impaired CVR there will be diminished blood flow response following neuronal activation, and that these areas would appear as false‐negative tests on BOLD fMRI. Materials and Methods: Patients with steno‐occlusive disease and unilateral hemodynamic impairment received a standardized hypercapnic stimuli while being imaged with BOLD fMRI to generate CVR maps. These were compared to traditional BOLD fMRI maps of neuronal activation in the motor cortex in response to a motor task. Results: Neuronal activation from the motor task was found to be linearly correlated with CVR ( n = 11 patients, R = 0.82). Regions with positive (normal) CVR showed positive activation on BOLD fMRI, while regions with negative CVR had attenuated neuronal activation on BOLD fMRI. Conclusion: In areas with cerebrovascular disease where CVR is impaired, there is uncoupling of neuronal activation and blood flow that confounds traditional BOLD fMRI. CVR mapping is a noninvasive MRI‐based imaging technique that can provide information about the vascular reactivity of the brain that is important to consider when interpreting traditional BOLD fMRI studies. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:1448–1455.